Development of Electronic Student Worksheets Based on Ethnophysics on the Pletokan Bamboo Game to Improve Problem-Solving Skills of High School Students on Parabolic Motion Material - Septy Kurrota A’yun; Nadi Suprapto; Pretty Oktianti Menur Kusuma Putri (Studies in Philosophy of Science and Education, 2025)
Ethnophysics is a learning approach that connects culture with the concept of physics. One example of ethnophysics is the bamboo pletokan game. Bamboo pletokan is a traditional game originating from Betawi with the basic material for making this game coming from bamboo. This study aims to produce an ethnophysics-based E-Worksheet on the bamboo pletokan game to improve the problem-solving abilities of high school students on the material of parabolic motion as a learning medium reviewed from the eligibility criteria, namely valid, practical, and effective. The method used in this study is Research and Development (R&D). This method is used to develop a product and test the results of the product. This study uses the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development design. The results of this study produce an ethnophysics-based E-Worksheet on the bamboo pletokan game with an Average E-Worksheet Validity Score in the very valid category. Thus, the ethnophysics-based E-Worksheet on the bamboo pletokan game can be utilized.